2011
DOI: 10.1117/1.3652712
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength selection in measuring red blood cell aggregation based on light transmittance

Abstract: Abstract. The reversible aggregation of red blood cells (RBC) is of current basic science and clinical interest. Using a flow channel and light transmittance (LT) through RBC suspensions, we have examined the effects of wavelength (500 to 900 nm) on the static and dynamic aspects of RBC aggregation for normal blood and suspensions with reduced or enhanced aggregation; the effects of oxygenation were also explored. Salient observations include: 1. significant effects of wavelength on aggregation parameters refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The properties of flowing blood have been investigated in vitro using microscopy, scatterometry, absorptiometry, laser diffraction and high-resolution SD-OCT (Schmid-Schoenbein & Wells 1969;Bitbol 1986;Ninomiya et al 1988;Fujii et al 1999;Enejder et al 2003;Friebel et al 2007;Baskurt et al 2009;Cimalla et al 2011;Nam et al 2011;Uyuklu et al 2011). Because the effective particle size is high in stagnant blood, where erythrocytes form aggregates, there are fewer reflecting surfaces in stagnant than in flowing blood.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of flowing blood have been investigated in vitro using microscopy, scatterometry, absorptiometry, laser diffraction and high-resolution SD-OCT (Schmid-Schoenbein & Wells 1969;Bitbol 1986;Ninomiya et al 1988;Fujii et al 1999;Enejder et al 2003;Friebel et al 2007;Baskurt et al 2009;Cimalla et al 2011;Nam et al 2011;Uyuklu et al 2011). Because the effective particle size is high in stagnant blood, where erythrocytes form aggregates, there are fewer reflecting surfaces in stagnant than in flowing blood.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because the effective particle size is high in stagnant blood, where erythrocytes form aggregates, there are fewer reflecting surfaces in stagnant than in flowing blood. Thus, overall reflectivity is low and light transmission is high in stagnant blood (Ninomiya et al 1988;Fujii et al 1999;Enejder et al 2003;Baskurt et al 2009;Cimalla et al 2011;Uyuklu et al 2011). When blood is set in motion in a tube, erythrocyte aggregates dissolve and the erythrocytes assume a non-random spatial orientation, leading to optical anisotropy (variation in optical properties with the direction of observation) and increased backscattering of light at right angles to the direction of flow.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From light transmission and reflectance, many parameters could be extracted to describe the rheological properties of blood including the rate of aggregation and sedimentation [7]. Later on, Oguz K. Baskurt et al used the same technique to monitor erythrocytes aggregation under different light wavelengths to optimize the conditions that give the best investigation of erythrocytes characterizations [21,23]. The wavelength survey was done previously by Oguz K. Baskurt et al and they found the best wavelength used to study light transmission through blood was 800 nm [23].…”
Section: Resultsmentioning
confidence: 99%
“…Different techniques have been used to monitor erythrocytes aggregation using light transmission, and different parameters were used to describe the aggregation rate and intensity [7,[21][22][23]. Technique established by M.R.…”
Section: Resultsmentioning
confidence: 99%
“…The analyzer contains a light-emitting diode (VSMG2700, Vishay) in the near-infrared (NIR) band (wavelength = 830 nm) and a photodetector (VEMT4700, Vishay), former at the top and latter at the bottom of the chip, respectively. Using NIR light, the optical transmission of hemoglobin is minimized, and thus higher transmission signal is obtained (Uyuklu et al 2011). For comparison of ESR results Fig.…”
Section: Measurement Systemmentioning
confidence: 99%